Multi-level linear programming subject to addition-min fuzzy relation inequalities with application in Peer-to-Peer file sharing system - Yang, Xiao-Peng; Zhou, Xue-Gang; Cao, Bing-Yuan (Journal of intelligent & fuzzy systems, 2015)
Abstract Multi-level linear programming problem subject to addition-min fuzzy relation inequalities is introduced to characterize a kind of optimization models in BitTorrent-like Peer-to-Peer file sharing systems. Based on some theorems, which contribute to the resolution of the proposed problem, we develop a novel algorithm to find the unique optimal solution. A practical application example is presented to illustrate the feasibility and efficiency of the algorithm.